Change in elastic modulus during fatigue bending and torsion of a polymer reinforced with continuous glass fibers. (August 2022) - Głowacka, Karolina; Kurek, Andrzej; Smolnicki, Tadeusz; Łagoda, Tadeusz; Osiecki, Tomasz; Kroll, Lothar
Highlights: The change in this modulus can be an indicator of fatigue in anisotropic materials such as composites. No papers, that would characterize the change of elastic modulus of composites in cyclic bending and torsion. The decrease in the shear modulus of transverse elasticity is greater, the larger the amplitude of the shear strain is applied. The larger the amplitude of normal strain (in bending), the faster the decrease in bending moment occurs. Abstract: The paper emphasizes the fact that in the case of composite materials which are characterized by anisotropy, unlike classic isotropic materials, the modulus of elasticity changes its value when the degree of damage changes. Moreover, a decrease in this modulus can characterize the degree of material damage. The literature on this phenomenon was analyzed. However, the vast majority of studies leading to the description of changes in the stiffness of the material have so far been carried out only for uniaxial tension–compression. One case was also found where the authors performed a similar analysis for the material subjected to torsion. It was found that such analysis has not yet been performed for pendulum bending, which is a very common type of load in structural elements. Based on the authors' own experimental research for cyclic pendulum bending and double-sided torsion of specimens made of polyamide PA6, reinforced with continuous glass fibers, it was found that, as in the case of uniaxial tension–compression, as the degree of damage increases, there is also a decrease in both Young's modulus for bending and the shear modulus for torsion.